Persistence with medication and overactive bladder: an ongoing challenge. (3rd July 2016) - Wagg, Adrian
ABSTRACT: Introduction : For optimum results from pharmacological management of overactive bladder, adherence to prescribed medication is required. Overactive bladder treatment has been compromised by low adherence and persistence to medications, losing many people who might benefit from treatment and exposing them to unnecessary consequences of their disease. Areas covered : This narrative review examines what is known about adherence and persistence with treatment and, drawing evidence from other disease areas suggests factors which might be modifiable to improve the situation. A structured search of PubMed using the terms persistence, adherence, overactive bladder, urgency incontinence, and chronic conditions, was performed and added to as themes from exiting data emerged. Expert commentary : Adherence has traditionally been poor in this disease area with limited understanding of the modifiable factors underlying the observation. Increased understanding of the nature of the underlying disease should allow adoption of strategies tested in other disease areas.